Clinical manifestation of Hurler syndrome in a 7 year old child - S Sharma; J R Sabharwal; P Datta; S Sood (Wolters Kluwer Medknow Publications, 2012)
Mucopolysaccharidosis type I (MPS I H, Hurler syndrome) is a rare autosomal recessive inborn deficiency in the metabolism of glycosaminoglycans (GAGs) heparan sulfate and dermatan sulfate, resulting from deficiency of Alpha-L-iduronidase enzyme. This condition is characterized by accumulation of incompletely degraded glycosaminoglycans into various organs of body, which leads to impairment of organs and body functions. Such children appear nearly normal at birth; however, if left untreated, show a progressive mental and physical deterioration leading to death due to cardiorespiratory failure before the second decade of life. Pedodontists have a role for early diagnosis, rendering corrective and preventive treatment to the developing dentition, and referring the patient to the concerned specialities. An interesting case of a seven year old boy with a combination of skeletal, neurological, ophthalmologic, oro-dental and radiological findings of this diverse and devastating clinical entity with MPS I-(Hurler syndrome) has been presented here in this case report.